2014
DOI: 10.3808/jei.201400280
|View full text |Cite
|
Sign up to set email alerts
|

State and Parameter Estimation in Three-Dimensional Subsurface Contaminant Transport Modeling using Kalman Filter Coupled with Monte Carlo Sampling

Abstract: CT. Accurate con f mathematical m ic models do no atially and temp contaminant pred ed with Monte C oise to reflect re de the filter at ev te Carlo sampling ter coupled with M n Absolute Error e Carlo sampling n filter coupled w n Absolute Error ter to the observat Kalman filter, pa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Over the past decades, numerical efforts were made in dealing with uncertainties in water quality management, such as Monte Carlo simulation, Bayesian statistics, and stochastic programming (Assumaning and Chang 2014;Ahmadi et al 2015). Bayesian analysis is effective in evaluating the probabilistic risk of water quality management through estimating unknown parameters in terms of posterior joint distributions, which incorporate the information of prior distributions (e.g., existing expert knowledge and experiences) and observed data (Qian et al 2005;Malve and Qian 2006;Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, numerical efforts were made in dealing with uncertainties in water quality management, such as Monte Carlo simulation, Bayesian statistics, and stochastic programming (Assumaning and Chang 2014;Ahmadi et al 2015). Bayesian analysis is effective in evaluating the probabilistic risk of water quality management through estimating unknown parameters in terms of posterior joint distributions, which incorporate the information of prior distributions (e.g., existing expert knowledge and experiences) and observed data (Qian et al 2005;Malve and Qian 2006;Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models have widely been used for analyzing water balance, forecasting long-range streamflow, predicting real-time flood, and investigating climate-change impact in watershed management because of the increasing availability of digital elevation models (DEMs), geographical information system (GIS), remote sensing (RS), and terrain analysis tools over a broad range of scales (Vincendon et al, 2010;Assumaning and Chang, 2014;Zhang et al, 2014). However, hydrological models often encounter substantial uncertainties with respect to the input data, initial and boundary conditions, model structure, and parameters due to insufficient of observation data, difference in spatiotemporal scale between the model and measurements and simplification of physical processes within the model (Salamon and Feyen, 2009;Jordan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the ongoing climatic changes is very important for human subsistence and sustainable development of the economy and society (Jordan et al, 2014;Jozsa et al, 2014;Shi et al, 2014;Wang et al, 2015b). Recent studies suggested that the change in climate extremes is particularly notable (Alexander et al, 2006;Assumaning and Chang, 2014). From a global perspective, changes in climate extremes have led to many serious consequences due to their direct and indirect effects on the physical, chemical and biological processes of other components of the Earth system.…”
Section: Introductionmentioning
confidence: 99%